PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE (GCG) TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2018 - Dwi Mila Oktaviani; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe purpose of this study was to evaluate the effect of good corporate governance mechanisms on the financial performance of manufacturing companies in the food and beverage sector which were listed on the Indonesia Stock Exchange in the 2016-2018 period. The independent variables in this study consisted of an independent board of commissioners, managerial ownership and an audit committee. While the dependent variable is the company's financial performance as measured by Return On Assets (ROA). The data analysis method used is multiple linear regression analysis. Sampling using a purposive sampling method and obtained 13 companies from 24 manufacturing companies in the food and beverage sector in accordance with the criteria to be used as research objects. Based on the research, it is known that the independent board of commissioners, managerial ownership and audit committee simultaneously influence the financial performance of companies listed on the Indonesia Stock Exchange in the period 2016-2018. But partially the independent board of commissioners has a negative effect on financial performance. While managerial ownership and audit committees do not affect financial performance. With an R Square value of 38.9% which is where the dependent variable is affected by the independent variable. While the remaining 61.1% is influenced by other variables not used in this study.  Keywords: Dewan Komisaris Independen, Kepemilikan Manajerial, Komite Audit, Kinerja Keuangan (ROA).